1975
DOI: 10.1146/annurev.me.26.020175.000301
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response to Infection

Abstract: A generalized infectious process leads to a broad and complex array of metabolic responses within the host. Certain of these responses have a direct causal relationship to the interactions of body cells with invading microorganisms or their products, or to specific host defensive mechanisms. Other host metabolic responses have less clearly defined roles although they involve many tissues and seem to be initiated and regulated by certain hormones-like endogenous mediators. These latter responses contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
118
0
3

Year Published

1983
1983
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(122 citation statements)
references
References 0 publications
1
118
0
3
Order By: Relevance
“…23,24 Our findings, that reduced HDL level was positively associated with hepatitis C infection and inversely associated with hepatitis B infection (albeit nonsignificantly), have two possible explanations. First, this may be due to proinflammatory cytokines, such as interleukin-6 and tumor necrosis factor (TNF) that are well documented to be positively associated with MS. By relating blood profiles to circulating cytokines in patients with chronic viral hepatitis due to HBV or HCV infection, Fabris et al 25 found that the differences between HBV and HCV in terms of the mechanism of liver damage and viral clearance manifested by the levels of circulating cytokines were related to differences in blood lipids profiles such as HDL.…”
Section: Dyslipidaemiamentioning
confidence: 73%
“…23,24 Our findings, that reduced HDL level was positively associated with hepatitis C infection and inversely associated with hepatitis B infection (albeit nonsignificantly), have two possible explanations. First, this may be due to proinflammatory cytokines, such as interleukin-6 and tumor necrosis factor (TNF) that are well documented to be positively associated with MS. By relating blood profiles to circulating cytokines in patients with chronic viral hepatitis due to HBV or HCV infection, Fabris et al 25 found that the differences between HBV and HCV in terms of the mechanism of liver damage and viral clearance manifested by the levels of circulating cytokines were related to differences in blood lipids profiles such as HDL.…”
Section: Dyslipidaemiamentioning
confidence: 73%
“…In evaluating the significance of these observations to the systemic actions of TNF, it is useful to consider the integrative role that TNF plays in promoting the acute-phase response (53) to infections and invasive stimuli, such as cancers. During the acute-phase response accelerated net breakdown of skeletal muscle and fat occurs with a concomitant shift to anabolic metabolism in the liver, to support the synthesis of acute-phase reactant proteins, as well as to bone marrow and wounds, for cellular proliferation within the immune system and for healing of injured tissue (53)(54)(55)(56)(57)(58)(59). These metabolic alterations represent a reprioritization of carbon and energy utilization in the injured or septic animal for survival.…”
Section: Discussionmentioning
confidence: 99%
“…One of the biochemical derangements that frequently is noted in infected m a m m a l s is a decrease in the ability of insulin to promote glucose uptake and to stimulate anabolic processes (1,2). A compensatory hyperinsulinemia results.…”
mentioning
confidence: 99%